TOTAL ECONOMIC VALUE OF ENVIRONMENTAL SERVICES, KAMPUNG BLEKOK, SITUBONDO - Ghina Salsabila; Amir Syarifuddin; Febri Arif Cahyo W. (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Blekok tourism village has become an ecotourism-based mangrove conservation area based on Situbondo Regent Regulation No. 13 of 2017. In less than 30 years, the mangrove forest has decreased by 50% this is due to the rapid population growth and lack of information from the community around the mangrove forest area. Decreasing the quality and quantity of mangroves can have an impact on the survival of the surrounding community and ecosystems that have been formed previously, so calculations are needed as a reference in the use of environmental services in the mangrove forest area. The purpose of this study is to determine the value of direct, indirect and optional economic benefits and to determine the value of the total economic benefits of the mangrove ecosystem economy. The method used was observation and interviews as primary data and literature studies as secondary data. The results obtained are the value of direct benefits of IDR. 681.284.900,00 per year obtained from the catch of crabs and ecotourism. The value of indirect use is obtained as much as IDR. 87.336.000,00 per year which is obtained from catching fish and making breakwaters. The value of choice is IDR. 1,399,923.00 (1 USD= IDR. 14.814,00. The total economic value generated by the mangrove forest area of ​​Kampung Blekok is IDR. 1.027.904.350,00 per year. Keywords: Blekok Village, economy, mangrove forest